Skiing Trauma and Safety: Twelfth Volume 1999
DOI: 10.1520/stp12358s
|View full text |Cite
|
Sign up to set email alerts
|

ACL Injury Mechanism in Alpine Skiing: Analysis of an Accidental ACL Rupture

Abstract: Knee injuries in alpine skiing, especially the rupture of the anterior cruciate ligament (ACL), are still the leading indication for surgical treatment. The boot-induced anterior drawer (BIAD) caused by the backward fall is one of the possible injury mechanisms. We investigated the landing of approximately 250 jumps to collect data for a computer model of the BIAD. During our experiments one test subject suffered an ACL rupture of his right knee. This accidental event was recorded on video for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Still, the biggest challenge is probably how to verify that the simulated injury pattern actually resembles what is experienced in real life. This is illustrated well with the experiment of Barone et al 86 If the injury had not occurred during their BIAD experiment, chances are that a ''solution'' not present in the real world could have been found, because the observed injury kinematics differed significantly from all the other noninjury ski jump landings.…”
Section: Mathematical Modellingsupporting
confidence: 78%
See 1 more Smart Citation
“…Still, the biggest challenge is probably how to verify that the simulated injury pattern actually resembles what is experienced in real life. This is illustrated well with the experiment of Barone et al 86 If the injury had not occurred during their BIAD experiment, chances are that a ''solution'' not present in the real world could have been found, because the observed injury kinematics differed significantly from all the other noninjury ski jump landings.…”
Section: Mathematical Modellingsupporting
confidence: 78%
“…It was concluded that the maximal tendon stress was considerably greater in sporting situations than in a static setting. In the study of Barone et al, 86 kinematic input to a simulation model was collected at the landing from a jump on a ski slope. The researchers intended, from the motion obtained, to simulate the so called boot induced anterior drawer (BIAD) injury mechanism.…”
Section: Injuries During Biomechanical Experimentsmentioning
confidence: 99%
“…Trunk lean was defined as the angle between the global vertical axis and the trunk segment. The between-subject SD of the trunk lean angle was derived from the study of Barone et al 23 amounting to 9.2°. This variation is comparable with other jump landing studies, where the corresponding values at initial ground contact have been reported between 7.1° and 13° 24–26.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al (2006a) also reported that the ACL could restrain both anterior and medial tibial translations, and medial tibial translation was found to be closely associated with valgus joint rotation (Li et al, 2007). It has previously been reported (Barone, Senner, & Schaff, 1999;Freudiger & Friederich, 2000) that anterior tibial translation is important in most critical load cases for ACL injuries sustained during ski-landing. Furthermore, it has been demonstrated that simulated quadriceps loading in cadaveric knees induced substantial anterior tibial translation of *2 cm, which resulted in ACL failure (DeMorat, Weinhold, Blackburn, Chudik, & Garrett, 2004).…”
Section: Introductionmentioning
confidence: 96%